Alternatif Pangan Sebagai Sumber Gizi Dengan Memanfaatkan Umbi Ubi Jalar Ungu (Ipomoea batatas L.) (Sumber Pangan Dengan Indeks Glikemiks Rendah) - Damaranie Dipahayu; Hilya Nur Imtihani (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2023)
Diabetes mellitus type 2 is the most common degenerative disease in Indonesia, so that the regulation of food intake is important. Food sources of carbohydrates with a low glycemic index (GI) can control blood sugar levels. GI is the rate at which food is absorbed into blood glucose. Purple sweet potato has a low GI so it is suitable as an alternative source of carbohydrates. Different cooking processes can affect the GI of the purple sweet potato, the frying technique produces the lowest GI compared to the boiling or baking technique. The manufacture of hybrid purple sweet potato flour is able to replace the use of wheat flour for processed food products. Hybrid purple sweet potato flour can increase the antioxidant content.